A simple and rapid method for simultaneous pre-concentration of eight trace-heavy-metals in water using 1-(2-pyridylazo)-2-naphthol and yttrium for X-ray fluorescence spectrometry. Issue 16 (21st August 2015) - Taguchi, Shigeru; Asaoka, Miyabi; Hirokami, Eiko; Hata, Noriko; Kuramitz, Hideki; Kawakami, Takanori; Miyatake, Ryuta
<x xml:space="preserve">Abstract</x> A simple and rapid pre-concentration technique for the simultaneous determination of eight trace heavy metals in water by energy-dispersive X-ray fluorescence spectrometry.